Deciphering the interplay between inflammation and dysregulated autophagy in lupus nephritis through network analysis and experimental validation - Zhang, Runrun; Lv, Xin; Sun, Qice; Huang, Wenhan; Zhao, Ting (Frontiers in Cell and Developmental Biology, 2026)
BackgroundAutophagy dysregulation plays an important role in the development and progression of lupus nephritis (LN). However, the key autophagy-related genes involved in LN and their underlying cellular mechanisms remain unclear. This study aims to systematically explore the autophagy-related molecular signatures of LN and to elucidate the relevant mechanisms.MethodsTranscriptomic data from LN and control kidney tissues were analyzed to identify differentially expressed genes (DEGs), followed by KEGG, GSEA, and GSVA enrichment. Autophagy-related DEGs (ARDEGs) were obtained by intersecting DEGs with autophagy gene sets. Hub genes were screened using PPI network analysis, cytoHubba algorithms, and WGCNA. Diagnostic performance was assessed by ROC curves and a nomogram. Single-cell datasets and qRT-PCR, pathology, TEM, and immunohistochemistry were used for validation. Functional assays were conducted in CIHP-1 podocytes with stable EGFR overexpression.ResultsA total of 445 ARDEGs were identified, enriched in autophagy, PI3K-Akt/mTOR, and MAPK pathways. Eleven hub genes were obtained, among which EGFR and RAF1 showed strong diagnostic value (AUC >0.90) and correlations with immune infiltration. Single-cell and experimental validation revealed elevated EGFR expression in LN. EGFR-overexpressing podocytes exhibited increased MDC fluorescence by flow cytometry, autophagosome accumulation by TEM, and a significant increase in LC3-positive puncta by confocal microscopy.ConclusionEGFR is a key regulatory factor related to autophagy in LN. The excessive activation of EGFR affects the autophagy of LN podocytes, providing new mechanistic insights and potential therapeutic targets for LN.